Tradisi Rebu Ngerana Pasca Perkawinan Pada Masyarakat Karo Sumatera Utara Perspektif ‘Urf - A. Millati Azka. A. M (Hukum Keluarga Islam IAIN LANGSA, 2020)
Rebu ngerana is a tradition that limits communication between three parties, including male and female in-laws, female in-laws with son-in-law, and fellow in-laws of different sexes. The purpose of this study is to analyze the meaning of the reconstructed tradition and its relationship with Islamic law. The method used is juridical empirical with the 'urf approach. The results of this study can be understood that the Karo people understand the tradition of rebu ngerana as an ancestral tradition that should be preserved because it has its own value in household life. However, in its current implementation, the Karo community in Ujung Teran village only imposes a tradition on their brother in-law to remind people to be aware of social principles in the way of life in a relationship. Meanwhile, in the view of ‘urf, the rebu ngerana tradition is included in the category of ‘urf sahih. So that it can be understood that this tradition has a relationship with the essence of marriage, namely maintaining self and family.